(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Today’s generation of students learn differently than those of the past, Technology is all around them, and access to a wealth of information is only a click away. Sported sebing and the consortium on found that 92% of students had technology in the home, but less than half used it for school work. Pedagogy must change with the times, when teachers continue to teach topics and skill that students may deem outdated and not applicable in the real world, students may lose motivation and interest as the intrinsic value of what was learned is lost by integrating technology into education, teachers will be able to motivate and include the entire spectrum of students. The main objectives of the study are to analyze the various dimensions of staff and student attitude towards technological changes, to find out the relationship between attitude towards technological changes in educational sector and demographic profile of the sample respondents and to analyse the consequences of attitude towards technology. The study was carried out with the staff and students attitude towards technological changes in Thoothukudi area. In and around Thoothukudi to select 120 colleges. It is decided to select 120 staff and students from various colleges and they are selected at random by adopting convenient sampling method. The result of ‘t’- test proved that monthly income, year of experience and kinds of device of the sample respondents and their level of attitude towards technology. The result of weighted arithmetic score states that 3.43 percent of the respondents are highly “There should be more education about technology”. The result of Garrett ranking is variation of rank as first place “Everyone needs technology” . Creative teaching should be adopted in educational institutional with the help of creative tools to stimulate creativity. There is need to incorporate audio and visuals materials during the courses of lecture delivery to motivate students to concentrate on their educational objectives